Comparison of Polyphenol Levels of Callus and Wild Type of Cat's Whiskers Plant ( Orthosiphon aristatus (Blume) Miq.) Purple Varieties - Fahrauk Faramayuda; Soraya Riyanti; Ari Sri Widyaswari; Zaini Alfahmi; Sultan Salahudin Jamal; Totik Sri Mariani; Elfahmi Elfahmi; Sukrasno Sukrasno (Green Engineering Society, 2022)
The cat's whiskers plant ( Orthosiphon aristatus (Blume) Miq) that grows in Indonesia has white flowers, purple flowers, and white flowers with purple patterns. The quality of the secondary metabolite content of each cat's whiskers plant is different because it depends on environmental influences such as rainfall or soil mineral content. Plant tissue culture methods such as callus culture or cell culture are used to overcome these obstacles because these methods do not depend on the environment and can produce secondary metabolites such as those produced by the original plant. Cat's whiskers contain the main secondary metabolite compounds: rosmarinic acid, eupatorin, and sinensetin. Rosmarinic acid belongs to the phenolic group, while sinensetin and eupatorin are flavonoids. This study aimed to determine the total levels of polyphenols and flavonoids in purple cat whiskers and determine the ratio of secondary metabolites of cat whiskers callus with wild-type plants—determination of polyphenol content using Folin Ciocalteau reagent. Determining flavonoid levels is based on colorimetry using AlCl 3 reagent, specific for flavone and flavonol compounds. The levels of polyphenols contained in the ethanolic extract of callus and cat whiskers of the purple variety were 16.056 ± 0.204 mgQE/g and 30.780 ± 0.425 mgQE/g, while the polyphenol content of the callus ethyl acetate extract and the purple variety of cat whiskers leaves was 15,489 ± 0.425 mgQE/g and 13,262 ± 0.044 mgQE/g. The levels of flavonoids contained in the ethanol extract of the cat whiskers leaf were 1.39±0.03 mgQE/g and callus 0.16±0.02 mgQE/g in the ethyl acetate extract of the leaves of the cat whiskers 2.16±0.012 mgQE/g and callus 2.24±0.010 mgQE/g. The polyphenols and flavonoids in the callus ethyl acetate extract were more significant than the ethyl acetate extract of the purple variety ( wild type ) cat whiskers leaf.